Does Internet Use Affect Air Pollution? Evidence from OECD Countries - Unzule Kurt; Cuneyt Kilic; Ahmet Tayfur Akcan (International Journal of Energy Economics and Policy)
This study aims to analyze the relationship between the use of the internet, which has an important place in information and communication, and air pollution (Carbon Dioxide Emissions-CO2). In this context, the relationship between the variables for the 1994-2019 period in 28 OECD countries selected was tested with the help of a panel data analysis with Fourier functions (Fourier unit root test, panel Fourier cointegration test and panel Fourier causality test). The results of the analysis show that internet use reduces air pollution, while economic growth increases air pollution. The results of the Panel Fourier Granger Causality test revealed a bidirectional causality relationship between internet use and air pollution and a unidirectional causality relationship from air pollution to economic growth throughout the panel. The analysis results present a policy proposal to the governments of OECD countries that they can reduce air pollution by investing in information and communication technologies (ICT) in their economic growth processes.